ChemInform Abstract: Palladium‐Catalyzed Decarboxylative Arylation of Benzoylacrylic Acids Toward the Synthesis of Chalcones. Issue 37 (22nd August 2013) - Unoh, Yuto; Hirano, Koji; Satoh, Tetsuya; Miura, Masahiro
Abstract Two simple routes to synthetically and biologically important chalcones are reported.